2019
DOI: 10.1088/1742-6596/1378/4/042016
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energetics Effects on Mechanical Strength of Fibre Reinforced Polymer Matrix

Abstract: Surface energetics effects on the mechanical strength of fibre reinforced polymer matrix been studied employed the manual scraper mechanism in extracting fibre from plantain pseudo-stem and was treated with nine different treatments. Cylindrical shape mould was prepared for mechanical test samples with continuous and unidirectional aligned fibres. Two probe liquids; water and glycerol were used in contact angle measurement for all the treated and untreated samples. The contact angle data was used for the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The contact angle was measured to determine when the modified FVB is easily wetted by a liquid; meanwhile, the value obtained is 24.02° with treatment H ( Table 2 ), which is much lower than the contact angle of bamboo, jute, ramie, and kenaf [ 4 , 32 ]. The modification of the combination of NaOH+Na 2 SO 3 decreased the contact angle compared to the water immersion treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle was measured to determine when the modified FVB is easily wetted by a liquid; meanwhile, the value obtained is 24.02° with treatment H ( Table 2 ), which is much lower than the contact angle of bamboo, jute, ramie, and kenaf [ 4 , 32 ]. The modification of the combination of NaOH+Na 2 SO 3 decreased the contact angle compared to the water immersion treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Several types of research studies have been carried out on natural fibers using a chemical treatment to modify the surface structure and improve the compatibility between adhesive and raw material. This includes the use of alkali modification in natural fibers due to the convenience and simplicity of its application [ 4 , 5 ]. Previous research studies have used sodium hydroxide (NaOH); however, the combination of NaOH+Na 2 SO 3 as a chemical for modification has not been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to assess the extent of variation of elastic properties in plantain fiberreinforced polyester composites to guard against out of plane failure during structural applications. Unfortunately most studies involving plantain fiber-reinforced composites has dwelt on assessment of tensile, flexural and hardness properties [32], optimization of hardness strengths [33], effect of water and organic extractives removal [34], effects of fiber extraction techniques [35], optimization of flexural strength [36], compressive and impact strength evaluation [37][38][39], effect of high-frequency microwave radiation [40], effect of chemical treatment on the morphology [41], implications of interfacial energetics on mechanical strength [42]. Although Ihueze, Okafor and Okoye [43] has reported the longitudinal (1) and transverse (2) properties of plantain fiber-reinforced composites in Figure 1, there is still need to establish the essential elastic constants at directions other than the material axis directions 1-2.…”
Section: Background To Plantain Cultivation and Utilization As Reinfomentioning
confidence: 99%
“…These products include palm trees, rice, sugar cane, bagasse, coconut fibre and so on. [1][2][3] To get these products to the final consumers, several agricultural activities are involved; cultivation, harvesting and processing. These activities are accompanied by the generation of quite a chunk of agricultural waste.…”
Section: Introductionmentioning
confidence: 99%
“…The current research trend is to use industrial and agricultural waste as a raw material source for composite development. 18,19 Further studies have shown that natural fibres pose good engineering properties for application in almost all engineering sectors. 20 Ceiling boards are needed in houses to reduce heat and sound while also adding aesthetic value.…”
Section: Introductionmentioning
confidence: 99%